MENERAPKAN MODEL PORTOFOLIO BASED LEARNING UNTUK MENINGKATKAN HASIL MENGAJAR GURU - Erlinda Erlinda (JURNAL PENA EDUKASI, 2019)
Abstract: The level of mastery of teacher teaching results before the action was carried out was 82.5% (Of the 40 teachers 33 people who completed study). Then in the first (first) cycle, the teacher's completeness rate became 77.5% (out of 40 teachers who completed 31 people). Then in the second cycle (two) after further action is taken as a result of reflection on the first cycle the percentage of teacher completeness level becomes 100%. The teacher's activities in learning Biology after school actions in the first cycle and second cycle increased. In the first cycle the average teacher attendance was 90% and in the second cycle 97.5%. Likewise in conducting learning activities Teachers have a large responsibility, especially in the collection of assignment documents. Teachers with a portfolio learning model have conducted independent learning. Keywords: Portofolio Based Learning, Abstrak: Tingkat ketuntasan hasil mengajar guru sebelum dilaksanakan tindakan adalah 82,5 % (Dari 40 orang guru 33 orang yang tuntas belajar). Kemudian pada siklus I (pertama), tingkat ketuntasan guru menjadi 77,5 % (dari 40 jumlah guru yang tuntas 31 orang). Selanjutnya pada siklus ke II (dua) setelah dilaksanakan tindakan lebih lanjut sebagai hasil dari refleksi pada siklus I presentase tingkat ketuntasan guru menjadi 100 %. Aktivitas guru dalam belajar Biologi setelah dilakukan tindakan sekolah pada siklus I dan siklus II semakin meningkat. Pada siklus I rata-rata kehadiran guru 90 % dan pada siklus II menjadi 97,5 %. Demikian pula dalam melakukan aktivitas pembelajaran Para guru mempunyai tanggung jawab yang besar, khususnya dalam pengumpulan dokumen tugas. Para guru dengan model pembelajaran portofolio telah melakukan pembelajaran secara mandiri. Kata kunci: Portofolio Based Learning, Hasil Mengajar Guru